Studi Literatur: Peranan Kadar Serum Ferritin Tinggi Mempengaruhi Pertumbuhan pada Pasien Thalasemia β Mayor Anak - Namira Ramadanty; Tito Gunantara; Mirasari Putri (Bandung Conference Series: Medical Science, 2023)
Abstract. This literature study was conducted to collect adequate data regarding the role of high ferritin on child growth in patients with thalassemia major. The method used is through a literature study that collects several previous studies to determine the role of high ferritin on the growth of children in patients with Thalassemia B Major. The results of this study can be used to measure excess iron in the body by measuring ferritin levels in plasma. If iron swelling occurs in the pituitary gland, it will interfere with the secretion of Growth Hormone (GH), Thyroid-Stimulating Hormone (TSH), and Adrenocorticotropic Hormone (ACTH) so that growth and development will be disrupted. Thus it can be concluded that high ferritin levels have an important role in the growth of children in patients with Thalassemia B Major. Abstrak. Studi literatur ini dilakukan untuk mengumpulkan data yang memadai mengenai peranan Ferritin tinggi terhadap Pertumbuhan Anak Pada Pasien Thalasemia B Mayor. Metode yang digunakan adalah dengan melalui studi literatur yang mengumpulkan beberapa penelitian terdahulu untuk mengetahui peranan ferritin tinggi terhadap pertumbuhan Anak Pada Pasien Thalasemia B Mayor. Hasil dari penelitian ini dapat digunakan untuk mengukur kelebihan besi pada tubuh adalah dengan mengukur kadar Feritin dalam plasma. Apabila terjadi penumpukan besi pada kelenjar hipofisis, akan mengganggu sekresi dari Growth Hormone (GH), Thyroid-Stimulating Hormone (TSH), dan Adrenocorticotropic Hormone (ACTH) sehingga pertumbuhan dan perkembangan akan terganggu. Dengan demikian dapat disimpulkan bahwa kadar ferritin tinggi memiliki peranan penting terhadap Pertumbuhan Anak Pada Pasien Thalasemia B Mayor.